Oat bran extract (Avena sativa L.) from food by-product streams as new natural emulsifier. (August 2018) - Ralla, Theo; Salminen, Hanna; Edelmann, Matthias; Dawid, Corinna; Hofmann, Thomas; Weiss, Jochen
Abstract: Natural emulsifiers have become of increasing interest within the food and beverage industry. Oat bran is a natural side-stream product produced during oat refinement that may be used to obtain amphiphilic extracts. Our hypothesis was that the oat bran extract is rich in surface-active and amphiphilic oat saponins and proteins that can form and stabilize emulsions. For this, we examined the surface activity of oat bran extract at oil-water and air-water interfaces, its ability to form oil-in-water emulsions and their stability against various stress tests. The highly surface-active oat bran extract acted as an ionic emulsifier, forming highly negatively charged submicron-sized emulsion droplets. These emulsions were stable over a wide range of pH (4–9), heat treatment (≤50 °C), and during storage at ≤25 °C up to 42 days. However, the emulsions showed instability at pH 2–3, at high ionic strengths, and during freeze-thawing. The formation and stability of the emulsions is related to interfaces containing oat saponins or oat saponin-protein complexes rather than a protein layer. These findings show that oat bran extract is a highly promising natural emulsifier, providing the food and beverage industry with a viable substitute to traditional emulsifiers. Graphical abstract: Image 1 Highlights: Oat bran extract effectively reduced interfacial tension. Oat bran extract formed small emulsion droplets. The emulsions were stable against a range of pH, heat, and storage time stresses.